2021
DOI: 10.1002/psc.3362
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembling systems comprising intrinsically disordered protein polymers like elastin‐like recombinamers

Abstract: Despite lacking cooperatively folded structures under native conditions, numerous intrinsically disordered proteins (IDPs) nevertheless have great functional importance.These IDPs are hybrids containing both ordered and intrinsically disordered protein regions (IDPRs), the structure of which is highly flexible in this unfolded state. The conformational flexibility of these disordered systems favors transitions between disordered and ordered states triggered by intrinsic and extrinsic factors, folding into diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 178 publications
0
12
0
Order By: Relevance
“…[39,40] Therefore, ELPs are regarded as intrinsically disordered proteins (IDPs) that retain functionality despite the lack of a single orderly structure. [41,42] Even in nonrandom structures above T t , ELPs can exist as a wide range of protein structures, including those partially structured in the form of premolten globules or molten globules rather than a single ordered structure. [43] Therefore, substitution of guest residues can affect the self-assembling abilities of ELPs by altering the interactions between peptide molecules or between peptides and solvent molecules, instead of controlling the tertiary structure of ELPs.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] Therefore, ELPs are regarded as intrinsically disordered proteins (IDPs) that retain functionality despite the lack of a single orderly structure. [41,42] Even in nonrandom structures above T t , ELPs can exist as a wide range of protein structures, including those partially structured in the form of premolten globules or molten globules rather than a single ordered structure. [43] Therefore, substitution of guest residues can affect the self-assembling abilities of ELPs by altering the interactions between peptide molecules or between peptides and solvent molecules, instead of controlling the tertiary structure of ELPs.…”
Section: Introductionmentioning
confidence: 99%
“…T t is often used as an indicator of self-assembling ability, and the low T t value indicates potent self-assembling ability. 27,44,42 Although it is known that shortening the peptide length reduces the selfassembling property of ELPs, we found that short ELP analogues, namely, B and C, showing self-assembling properties could be obtained by using these potential motifs as a repetitive unit. On the other hand, three shuffled analogues, D, F, and L, hardly dissolved in the phosphate buffer.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…Therefore, ELPs have been regarded as intrinsically disordered proteins (IDPs) that exhibit their functionality without forming a single orderly structure. 41,42 However, notably, some studies have mentioned that the turn structure that forms in the PG sequence is important for the self-assembly of ELPs. 43−45 On the other hand, it has been reported that the secondary structure of synthetic self-assembling ELPs is different from that of conventional ELP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Exosomes (Exos), a subclass of extracellular vesicles, have a crucial role in paracrine cell-to-cell interaction via the transfer of several signaling biomolecules [ 280 , 281 ]. These particles with an average diameter size of 50–150 nm can promote angiogenesis in ischemic organs [ 282 ]. It has been shown that Exos lack oncogenic and immunogenic features and can cross biological interfaces and thus distribute easily in the whole body [ 283 ].…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%